PKM pelatihan penggunaan Lembar Kerja Peserta Didik fisika berbasis keterampilan proses sains di SMAN 5 Kota Parepare - Mutahharah Hasyim; Ahmad Yani; Sidin Ali (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
The purpose of the training of the use of LKPD physics-based science process skills for students in SMAN 5 Parepare is to train and introduce scientific attitudes and process skills that are science on LKPD High School physics. The methods used are methods of practice, mentoring, and monitoring evaluation on the training of use of LKPD based on Science process skills (KPS). The external resulting from this activity is (i) improve the skills of the students ' science process through the administration of LKPD and (ii) skilled students perform practicum with KPS-based LKPD. The conclusion gained from this activity is (i) the knowledge of the students of SMAN 5 Parepare about the KPS-based LKPD increasing and (ii) the motivation and ability of the students to practice with the KPS-based LKPD increases.